Job crafting and job performance: The mediating effect of engagement - Moreira, Ana (2022)
The main purpose of this study was to investigate whether work engagement mediates the rela-tionship between job crafting and job performance. To this end, the following hypotheses were formulated: (1) job crafting establishes a positive and significant association with job performance; (2) job establishes a positive and significant association with work engagement; (3) work engage-ment establishes a positive and significant association with job performance; (4) work engagement mediates the association between job crafting and job performance. The sample was composedof 453 participants) working in organizations based in Portugal. The hypotheses formulated in this study were tested by performing simple and multiple linear regressions. The results indicated that only increasing structural job resources and increasing challenging job demands established a pos-itive and significant association with task performance. Increasing structural job resources, in-creasing social job resources, and increasing challenging job demands established a positive and significant association with citizenship performance and work engagement. Work engagement established a positive and significant association with task performance and citizenship perfor-mance. Only a partial mediating effect, through work engagement, was observed on the association between increasing challenging job demands and task performance, and between increasing social job resources and citizenship performance.